2012
DOI: 10.7314/apjcp.2012.13.3.931
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Cdc25B in Renal Cell Carcinoma is Associated with Decreased Malignant Features

Abstract: Cdc25 phosphatases are important regulators of the cell cycle. Their abnormal expression detected in a number of tumors implies that their dysregulation is involved in malignant transformation. However, the role of Cdc25B in renal cell carcinomas remains unknown. To shed light on influence on renal cell carcinogenesis and subsequent progression, Cdc25B expression was examined by real-time RT-PCR and western blotting in renal cell carcinoma and normal tissues. 65 kDa Cdc25B expression was higher in carcinomas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…CDC25B plays a minor role in the pathogenesis and/or progression of vulvar carcinoma, which has been associated with malignant features and aggressive cancer phenotypes but not independently correlated to prognosis 20. In contrast, we have identified that the expression of CDC25B was increased distinctively in carcinoma over that in the adjacent normal tissues, at both mRNA and protein levels, and there was a positive correlation between CDC25B expression and clinical stage and histopathologic grade of RCC 21. However, the mechanism that leads to the dysregulation of CDC25B within the specific context of tumor proliferation and progression has largely remained elusive.…”
Section: Discussionmentioning
confidence: 62%
“…CDC25B plays a minor role in the pathogenesis and/or progression of vulvar carcinoma, which has been associated with malignant features and aggressive cancer phenotypes but not independently correlated to prognosis 20. In contrast, we have identified that the expression of CDC25B was increased distinctively in carcinoma over that in the adjacent normal tissues, at both mRNA and protein levels, and there was a positive correlation between CDC25B expression and clinical stage and histopathologic grade of RCC 21. However, the mechanism that leads to the dysregulation of CDC25B within the specific context of tumor proliferation and progression has largely remained elusive.…”
Section: Discussionmentioning
confidence: 62%
“…Li et al (2011) found that high expression of CXC receptor 4 (CXCR4) was associated with not only increased risk for disease progression, but also worse OS of high-risk LARCC patients. Yu et al (2012) proved that knockdown of cdc25B in ccRCC is associated with decreased malignant features and cdc25B was an attractive prognostic marker for this tumor. Some other biomarkers were also found to be promising molecular predictor of tumor recurrence, such as RNA-binding protein IMP3 (Jiang et al, 2006), carbonic anhydrase 9 (Tostain et al, 2010), and P53 .…”
Section: Discussionmentioning
confidence: 95%
“…Once metastasis occurred, the patients with metastatic ccRCC would face a poor prognosis with a median survival of 6-10 months and a 10-20% 2-year survival rate (Janzen et al, 2003). In recent years, some prognostic markers for ccRCC, such as RALYL (Cui et al, 2012), CXCR4 (Li et al, 2011), Cdc25B (Yu et al, 2012), have appeared, but large-scale clinical application is impossible. Despite the continual progress in medical technology, the clinical characteristic of ccRCC is still difficult to predict (Wei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of CDC25B in renal cancer cells causes G2/M arrest, and subsequently induces cell apoptosis with concomitant reduction of the 14‐3‐3 protein. CDC25B knockdown is associated with a decrease in malignant features; for example, cancer cell migration and invasion . Furthermore, a selective inhibitor of CDC25 phosphatases; that is, Cpd5, might have potential as an anti‐neoplastic agent for RCC …”
Section: Pps In Genitourinary Cancermentioning
confidence: 99%